Perbedaan Abnormal Return sebelum dan sesudah pengumuman Rverse Split - , Adhika Priyotomo; , Prof. Dr. Marwan Asri, MBA. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Reverse split announcement is one of information that can lead to abnormal return of a stock. To see that it is done research that aims to identify whether the impact of announcements before and after the reverse split PT Smartfren there a significant difference in abnormal return. This study uses event study approach, where observations of abnormal return during the five days before the announcement of the reverse split, reverse split at the time, and five days after the announcement of the reverse split. This research is a case study that examines only one company, PT Smartfren Tbk. The data used in this study is secondary data in the form of daily stock price data when closing and daily stock price index. This test using paired sample t-test for different test before and after the reverse split. The results of this study indicate that there is no significant difference between the abnormal returns before and after the reverse split announcements caused investors to respond the same to the reverse split announcement, another alleged reverse split information may have been leaked before the announcement occurs. Leak may be caused by the General Meeting of holders of Shares carried out long before the day of the announcement and the news that the reverse split will be implemented so that the overall market had anticipated when they listed with a nominal price of a new one.